Nitrogenation Strategy for the Synthesis of N-containing Compounds - Jiao, Ning.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book focuses on direct nitrogenation strategies to incorporate one or more N-atoms into simple substrates especially hydrocarbons via C-H and/or C-C bond cleavage, which is a green and sustainable way to synthesize nitrogen-containing compounds. The book consists of seven chapters demonstrating interesting advances in the preparation of amines, amides, nitriles, carbamides, azides, and N-heterocyclic compounds and illustrating the mechanisms of these novel transformations. It offers an accessible introduction to nitrogenation reactions for chemists involved in N-compound synthesis and those interested in discovering new reagents and reactions. Ning Jiao is a Professor of Chemistry at Peking University, China.
Introduction -- Nitrogenation Strategy in Inorganic Chemistry -- Nitrogenation Strategy for the Synthesis Amines -- Nitrogenation Strategy for the Synthesis Amides -- Nitrogenation Strategy for the Synthesis Nitriles -- Nitrogenation Strategy for the Synthesis Carbamides -- Nitrogenation Strategy for the Synthesis Organic Azides -- Nitrogenation Strategy for the Synthesis N-heterocyclic Compounds.
Keywords: Organometallic chemistry .; Catalysis; Medicinal chemistry; Organometallic Chemistry; Catalysis; Medicinal Chemistry